Nonmalignant Central Airway Obstruction: Options for Challenging Cases - Abia-Trujillo, David; Fernandez-Bussy, Sebastian (Seminars in Respiratory and Critical Care Medicine, 2022)
Benign central airway obstruction is commonly referred as nonmalignant central airway obstruction (NMCAO). This is in part related to its lack of benign nature and significant life-quality impairment in patients. It is a pathologic entity with various etiologies and therefore a wide range of therapeutic options are available. Evidence regarding the optimal management that could provide a sustained restoration of airway patency is lacking. The lack of a common pathophysiologic pathway translating into a nonspecific symptom presenting as NMCAO has complicated treatment standardization and subsequently limited solid research to favor of one approach over another one. Our intent is to describe the limited evidence of the most utilized nonsurgical treatment for NMCAO as well as some upcoming promising therapeutic options such as mitomycin C injection, microdebrider, biodegradable stents, radiotherapy, Hybrid Knife, and endoluminal spray cryotherapy. Our goal with this manuscript is to motivate other authors to venture into prospective, multicenter, open-label trials aimed to describe long-term outcomes in patients with NMCAO.
Keywords: central airway obstruction; airway stenosis; nonmalignant; airway stenosis; central airway collapse